Міжнародні організації : методичні рекомендації до семінарських занять, самостійної та індивідуальної роботи (для здобувачів першого (бакалаврського) рівня вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії» освітньої програми «Міжнародні відносини та регіональні студії») - Панова, Ірина Олексіївна; Panova, Iryna O. (Харків : Харківський національний університет імені В.Н. Каразіна, 2023)
Видання містить програму навчальної дисципліни, методичні матеріали до семінарських занять, організаційно-методичні рекомендації до самостійної роботи здобувачів вищої освіти та проведення контролю знань, методичні рекомендації до написання науково-дослідних (індивідуальних) робіт, теоретичні питання для підготовки до підсумкового контролю. Методичні рекомендації розроблені для здобувачів першого (бакалаврського) рівня вищої освіти спеціальності 291 «Міжнародні відносини, суспільні комунікації та регіональні студії».

The publication contains the program of the academic discipline, methodical materials for seminar classes, organizational and methodical recommendations for the independent work of students of higher education and conducting knowledge control, methodical recommendations for writing scientific research (individual) works, theoretical questions for preparation for the final control. Methodological recommendations are developed for applicants of the first (bachelor) level of higher education in specialty 291 "International relations, public communications and regional studies".
International organizations: methodological recommendations for seminar classes, independent and individual work (for applicants of the first (bachelor) level of higher education, specialty 291 "International relations, public communications and regional studies" of the educational program "International relations and regional studies")
Навчальне видання. В авторській редакції
Keywords: Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::LAW/JURISPRUDENCE; міжнародних відносини; міжнародні організації; міжнародно-правову база; класифікація міжнародних організацій; моделювання схем проведення засідань; Організація Об’єднаних Націй (ООН); міжнародні економічні відносини; міжнародне економічне співробітництво; сучасні інтеграційні угруповання світу; міждержавні організації; галузевий рівень; регулювання економічних відносин; регулювання світової торгівлі; міжнародні валютно-фінансові організації; наддержавне регулювання світового господарства; міжнародні організації у сфері безпеки; проблеми та перспективи співробітництва України; функції та ролі міжнародних неурядових організацій; семінарські заняття; самостійна та індивідуальна робота; суспільні комунікації; регіональні студії; інтеграційні угруповання світу; international relations; classification of international organizations; modeling of meeting schemes; international economic relations; United Nations (UN); modern integration groups of the world; intergovernmental organizations; industry level; international organizations; integration groups of the world; regional studies; public communications; independent and individual work; international legal framework; seminar classes; functions and roles of international non- governmental organizations; problems and prospects of cooperation of Ukraine; international organizations in the field of security; supranational regulation of the world economy; international economic cooperation; regulation of economic relations; regulation of world trade; international monetary and financial organizations